Fractional 1064 nm picosecond laser and skin photoaging: in vivo evaluation of treatment effects with reflectance confocal microscopy. (19th May 2021) - Guida, S.; Fusano, M.; Pellacani, G.; Bencini, P. L.
ABSTRACT: Few studies showed the role of picosecond laser (PLS) in the treatment of skin photoaging signs. However, no studies have explored the microscopic effects of PSL in photoaging. The aim of this study is to preliminarily identify clinical variations induced by a 1, 064 nm Nd:YAG PSL on the décolleté area, then to apply the treatment protocol to treat facial photoaging and estimate the clinical and microscopic outcomes. A total of 10 consecutive patients with cutaneous photoaging were enrolled. Patients were treated 3 times at monthly intervals with the fractionated 1, 064 nm Nd:YAG PSL. In a preliminary phase, PSL treatment was performed on the décolleté to establish its efficacy and safety. Then, the same treatment protocol was applied to all the face and clinical and reflectance confocal microscopy (RCM) were analyzed, comparing baseline (T0) pictures and 4 months after the treatment (T1) ones. On the face, a reduction of dyschromia and wrinkles was observed at T1. Furthermore, the underlying RCM variations were revealed at different skin levels. Our results show the clinical and microscopic effectiveness and safety of the 1, 064-nm Nd:YAG PSL in the treatment of skin photoaging signs.